Copper catalyzed oxidative coupling reactions for trifluoromethylselenolations – synthesis of R-SeCF3 compounds using air stable tetramethylammonium trifluoromethylselenate1. Issue 21 (14th March 2015) - Lefebvre, Quentin; Pluta, Roman; Rueping, Magnus
<x xml:space="preserve">Abstract</x> The aerobic, room-temperature coupling of tetramethylammonium trifluoromethylselenate with readily available boronic acids, boronic esters, and terminal alkynes has been developed.